2011
DOI: 10.1186/1756-3305-4-45
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of distribution and efficacy of different spot-on permethrin formulations in dogs artificially infested with Dermacentor reticulatus

Abstract: BackgroundVarying reports concerning the duration and reliability of different permethrin preparations' efficacy can be found in the literature. The aim of this study was to investigate the dynamics of the distribution and efficacy of four different spot-on formulations with permethrin as the active ingredient formulated with different solvents. To examine the influence of these solvents on the speed of distribution and the acaricidal activity of permethrin in the coat, an in vivo study under laboratory condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…sanguineus, but it does not suppress infestation completely [20]. However, Lüssenhop et al demonstrated that in dogs treated with permethrinimidacloprid spot-on, most ticks were dead 6 h after experimental infestation with ticks of the genus Dermacentor reticulatus [21]. In fact, many dogowners who use the spot-on treatment report that it is not uncommon to find ticks attached to the dog, but that usually these ticks are dead.…”
Section: Discussionmentioning
confidence: 99%
“…sanguineus, but it does not suppress infestation completely [20]. However, Lüssenhop et al demonstrated that in dogs treated with permethrinimidacloprid spot-on, most ticks were dead 6 h after experimental infestation with ticks of the genus Dermacentor reticulatus [21]. In fact, many dogowners who use the spot-on treatment report that it is not uncommon to find ticks attached to the dog, but that usually these ticks are dead.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption that tick biting behaviour is not influenced with increasing distance from the application site [12] could thus be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no shift of the feeding ocation on treated dogs to places further away from the acaricide application sites (neck) was expected. According to Lüssenhop et al [12] the effect of acaricides is distributed homogeneously on the dog’s skin, indicating that there is no reduction of the concentration of the active component with increasing distance from the application site.…”
Section: Introductionmentioning
confidence: 99%
“…As this study was conducted with beagles only, the possibility of different results in other dog species with different coat lengths can not be excluded. In spite of the low concentration towards the end of the study, a sufficient acaricidal effect could be shown in a study with ticks which was simultaneously conducted on the same dogs (Lüssenhop et al. , 2011).…”
Section: Table Showing Permethrin Concentrations In μG/g Hair For Eamentioning
confidence: 99%
“…In conclusion, the additives 1-methoxypropan-2-ol, isopropyl myristate and 1-methyl-2-pyrrolidon do not significantly differ in their effect on the distribution and thus efficacy (Lü ssenhop et al, 2011) of permethrin in four commercially available formulations.…”
mentioning
confidence: 99%